ASSESSING THE IMPACT OF TECHNOLOGY ADOPTION ON PRODUCTIVITY OF PLANTAIN FARMERS IN NIGERIA - Osagie John Afodu; Olufunso Emmanuel Akinboye; A O Akintunde; L C Ndubuisi-Ogbonna; B A Shobo; O S Oyewumi (Socio-Economics/Agribusiness Department, 2021)
Sub-Saharan Africa has been plaque with food insecurity due to lack of adoption of modern technology to improve their productivity. Technology is the systematic application of scientific or other organized body of knowledge to practical purposes. This includes new ideas, inventions, innovations, techniques, methods and materials. Since increasing agricultural productivity is critical to meeting the continues rise in demand for food, agricultural technologies will play immense role in increasing the production of food. As a result, it is useful to examine the adoption of technologies among farmers. A multistage sampling technique was used for the selection of five hundred and fifty - six plantain farmers. The data were collected through the administration of a well-structured questionnaire on a cross-section surveyed of plantain farmers. The result of the study shown that educating the plantain farmers in Nigeria will enable them adopt new technologies which will enhance their productivity.